Chemical castration of small animals: where are we? - Aires Silveira , Vitória (Pubvet, 2021)
The great number of stray animals in Brazil and around the world is considered a public health issue due to the potential zoonotic disease transmission. As a solution, population control based on cost-effective, non-surgical methods of sterilisation without postoperative complications are explored. The goal of this review is to show the most used chemosterilants, illustrating their commercial availability. In male animals, several studies proved that permanent sterility involving the use of calcium chloride or zinc gluconate can be achieved. Also, these chemosterilants may be potentialized and side effects reduced depending on which diluent is chosen. In contrast, the studies in female animals are rare. The chemical method needs to be better divulged and to be applied in practice, while there is a need of further progress to its application in females.